Post Occupancy Evaluation of a Planned Community in Arctic Canada. - Bechtel,Robert B; Ledbetter,C Burgess (1980)
This report describes a post-occupancy evaluation of a small mining community in the high Arctic. Providing superior housing, having wives work and integrating singles, Inuits (the indigenous people) and families successfully established a viable community. Fewer problems were encountered than is usual in other isolated cold regions communities. The central focal point of the town, a large dome, was diluted by later construction of buildings housing separate recreational and social facilities. Since the buildings are too costly to remove, the only method of restoring the focal point is to build connecting links at upper levels of the recreational buildings. This would only restore the focal point to a fraction of its original effectiveness. Nanisivik is an important lesson for designing future cold regions communities. It provides a successful example of housing, organization of living groups, and integration of working and living environments, and a classic example of a missed focal point design. (Author)